2020
DOI: 10.31349/revmexfis.66.153
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear mixed convective nanofluid flow along moving vertical rough plate

Abstract: The objective of the current research paper is to investigate the effects of surface roughness on magnetohydrodynamic nonlinear mixed convection nanofluid flow over vertically moving plate. The highly coupled dimensional nonlinear partial differential equations (NPDE) are converted into dimensionless NPDE along with the boundary conditions with the help of non-similar transformations. The resulting set of dimensionless nonlinear PDE’s are solved by using Quasilinearization technique and implicit finite differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The surface roughness is modeled in terms of large frequency and low amplitude sinusoidal waves. The control equations representing the hybrid nanosuspension flow variations are [2,7,[42][43][44][45]:…”
Section: Mathematical Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The surface roughness is modeled in terms of large frequency and low amplitude sinusoidal waves. The control equations representing the hybrid nanosuspension flow variations are [2,7,[42][43][44][45]:…”
Section: Mathematical Analysismentioning
confidence: 99%
“…Patil et al [44] have investigated the nanosuspension combined convection motion over a rough sphere and their outcome reveals that with suitable choice of roughness and combined convection parameter the point of separation can be delayed. In addition, Patil et al [45] have analyzed nanoliquid motion about a moving plate and their outcome shows that the friction at the surface enhances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampath Kumar et al [32] inspected the stream of Jaffrey nano liquid, considering the impact of quadratic convection, MHD, nonlinear radiations, and multiple convected constraints. Patil and Kulkarni [33] probed the impact of surface ruggedness on MHD nonlinear convective nano liquid stream above a vertically moving plate. The comparative analysis for the linear and nonlinear buoyancy stream of hybrid nano liquid was explored by Kumar et al [34].…”
Section: Introduction Background Studymentioning
confidence: 99%
“…The appearance of such finely spaced microirregularities on the surface texture is known as surface roughness. Recent studies on surface roughness in mixed convection regimes can be found in References [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%